Analisis Aspek Kebahasaan dan Penyajian Materi pada Elemen Menulis Teks Pidato dalam Buku Teks Bahasa Indonesia Kelas VIII Kurikulum Merdeka - Tyas, Inno Cahyaning; Mutiah, Arju; Rahman, Adenarsy Avereus (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Language and material presentation are part of the textbook eligibility criteria. Both aspects can help achieve learning objectives, especially in textbooks. The use of language and the presentation of the right marteri will affect the effectiveness of learning in the classroom so that the meaning of the text content can be conveyed to students. The purpose of this study was to determine the accuracy of the linguistic aspects and presentation of material in the Indonesian language textbook for class VIII SMP Merdeka curriculum. This research method is a qualitative approach, Data and data sources are words, phrases, and sentences in the 8th grade Indonesian language book Merdeka Curriculum. The results and discussion of this study are based on the linguistic aspects and presentation of material in general, it meets the criteria of straightforward, communicative, dialogical language, motivating ability, and according to language rules. Likewise, the presentation of the material has adjusted to the Merdeka Curriculum. This can be adjusted to the CP and TP of the Merdeka Curriculum because the data source is an Indonesian language book by the Ministry of Education and Culture. So it can be concluded that the textbook linguistically and the presentation of the material have met the criteria.